Propuesta de un Plan de Marketing para el Turismo Comunitario del Cantón Saraguro, Provincia de Loja - Cobos Ramón, Laura María (2015)
The Ecuador by its geographic location has a great diversity of landscapes, ethnicities, traditions and customs. That is why tourism has become a major pillar for economic development because it creates major currencies for the country to improve the quality of life of Ecuadorians. Our country has 24 provinces, each with unique characteristics within it the Province of Loja comprised of its 16 cantons that attract the attention of tourists for the variety of both cultural attractions, as is natural. Canton Saraguro is located 64 km from Loja; It has a variety of unique attractions; currently the practice of Community Tourism has become an activity where community members are organized to provide services, offering their homes, customs, knowledge and way of life to those who come to live this experience, however, has not been released, therefore it became necessary to raise a "marketing plan proposed for Community tourism Canton Saraguro, Loja Province," the same as was done by signing an agreement between the National University of Loja and the Department of Intercultural Decentralized Autonomous Government of the Canton Saraguro, using the methodology and canvas ventures began with a diagnosis of tourism sector, developing basic strategic objectives for the proposed marketing plan to raise awareness of domestic and foreign tourists to practice it, to position Saraguro canton as a tourist destination. To fulfill the specific objectives developed work; making the diagnosis of the current situation of tourism, the proposal of a tourism marketing plan and socialize marketing plan to the relevant authorities; to implement these objectives deductive, inductive, descriptive and historical methods and techniques such as direct observation, interview and survey were used. The diagnosis of the current situation of community tourism in the Canton Saraguro, a study was performed by the macro and micro environment, the macro environment focused on the analysis of five factors: demographic, economic, political, cultural and technological development of the country and Canton Saraguro, surveys of the population using multiple choice questions. To study the micro environment manager interviews the head of Tourism Saraguro GAD were performed; and Mr. Luis Lozano representative of the Community Tourism Canton, who provided information about the benefits and limitations it has the sector in tourism; plus the collection of information was done by applying sheets attractions of the Ministry of Tourism which includes general information, geographic, tourist activities and recommendations that tourists should learn about each of the natural and cultural attractions of the canton . One of the key aspects in the development of the proposed marketing plan was the development of the SWOT matrix, began with the identification of external and internal factors, external opportunities and threats was set, and the internal strengths and weaknesses, I build a cross SWOT matrix, thus obtaining two strategic objectives: to design a promotion and publicity plan valued at $ 5,800.00 and tourism training plan aimed at families of community tourism centers to improve their services, valued at $ 797.50, so sources of employment will increase and thus strengthen tourism development. As a last specific objective socialization of this work to the relevant authorities of the Decentralized Autonomous Government of the Canton Saraguro, and representatives of the Community Tourism it was held in the premises of the Municipality of Saraguro, establishing important and fundamental contributions to the development of conclusions and recommendations Grade this job. As for the conclusions it is important to emphasize that realization of this type of research work to benefit more students because it is a requirement to pass the qualification cycle directly benefit the tourism development of the Canton.